Business Diversification and Financial Supply Chain Efficiency of Companies Listed on Ho Chi Minh City Stock Exchange - Nguyen, Anh Phong; Nguyen, Thi Hai Hang; Than, Ngoc Minh (International Journal of Supply Chain Management, 2020)
Abstract— This research evaluate the impact of business diversification of companies listed on HoSe from 2013 to 2017, the research has used balance panel data form of 145 listed enterprises. Business diversification is measured according to the Entropy index, measured by turnover in the Grade 2 subdivision and Level 4 subdivision according to Vietnam's industry standard. The results of the study showed that diversification would generally help improve financial efficiency, however, for those enterprises focusing on diversification outside the industry will reduce financial efficiency. In addition, the results of the study also showed that businesses increasing financial leverage for the purpose of expanding the left-sector business will be unstable, those businesses scaling up to strengthen the true diversification of businesses with experience will help increase their financial efficiency.